Functional-Semantic Potential of Verbal Collocations of Memory in Russian Media: Corpus Study - M. V. Milovanova; E. V. Terentyeva (Научный диалог)
This article represents the part of a collective study of verbal collocations of memory functioning in the Russian media. The authors focus on poly-aspect characteristics (structural, semantic and syntagmatic) of verb collocations with the key word pamyat’ “memory,” recorded in the Russian media of late 20th - early 21st centuries. The material for the study is the corpus of Russian newspaper texts from the University of Leeds and newspaper corpus of the National corpus of the Russian language. Using methods of analysis based on Loglikelihood score measures the patterns of representation of memory operations in the Russian language are determined. The authors characterize the selected subset of collocations that describe the different types of mnemonic processes, consider structural-semantic models implementing in collocations for each of the selected subgroups; characterize the nomination motive, associations and images that indicate the perception of memory as a discursive phenomenon. According to the results of complex analysis the conclusions are made about the functional-semantic potential of the verbal collocations of memory in contemporary Russian journalism. The article provides an example of a dictionary entry of ideographic comprehensive dictionary of Russian verbal collocations of memory, which macrostructure reflects an ontologically-driven classification of mnemonic processes, combining lexical units into semantic groups around key words in alphabetical order.